Regulation Simplification and Implementation of Regulatory Reform Agenda - Mohamad Iksan Maolana (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2018)
Nowadays, the conditions of regulation in Indonesia, from quatity perspective, are within the overregulated position or in other word, the number of regulation which exist is too excessive. Moreover, withn quality perspective, there are many inconsistent regulations, overlapping and contradicted each other. Those conditions have negative significant especially in its relationship with the investment climate and business competition in Indonesia. In last 2014, The President Joko Widodo has mandated the ministries to apply simplification of regulation through the pruning about 50% from 42000 regulations which currently prevail in Indonesia. This article aims to observe the significance of regulation simplification in Indonesia by draw the successful implementation of regulation simplification in South Korea. This article also discusses the steps which should be applied by the Indonesia government in order to implement the regulation simplification. In the last chapter, this article will portray the potential obstacles that will be faced by the government during the process of implementation of regulation simplification in Indonesia and also suggest the solution to answer those probs.